2013
DOI: 10.1159/000350360
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Central and Peripheral Fat Tissues on the Delayed Rectifier K<sup>+</sup> Outward Currents in Cardiac Myocytes

Abstract: Objectives: The amount of fat tissue is associated with an increasing incidence of cardiac arrhythmias. The purpose of this study was to investigate effects of adipocytokines from different body fat on delayed rectifier K+ outward currents (IK). Methods: H9c2 cells were treated with adipocytokine-free medium (the Adipo-free group) and with adipocytokines from epicardial (central fat group) and limb (peripheral fat group) rat fat tissues. IK, as well as expressions of Kv2.1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 24 publications
0
25
0
2
Order By: Relevance
“…Another study also revealed that a larger leg fat mass was associated with lower glucose levels, including fasting and postprandial glucose, particularly in women . Additionally, Lee and colleagues found that the amount of fat tissue in the central fat was associated with increased incidence of cardiac arrhythmias, compared with the PF group . These study results might provide some information for us to explain why PF plays a protective role in cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 78%
“…Another study also revealed that a larger leg fat mass was associated with lower glucose levels, including fasting and postprandial glucose, particularly in women . Additionally, Lee and colleagues found that the amount of fat tissue in the central fat was associated with increased incidence of cardiac arrhythmias, compared with the PF group . These study results might provide some information for us to explain why PF plays a protective role in cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 78%
“…Previous study showed that cardiac adipocytokines significantly decreased the membrane potential of delayed rectifier K + outward currents. 24 Some distinctive electrophysiological effects of pericardial fat could be considered for the pathogenesis of ventricular arrhythmia. In this study, we found that pericardial fat was significantly associated with the occurrence of VPBs.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al investigated the effects of adipocytokines from different body fats on delayed rectifier K + outward currents ( I Kr ) in cardiomyocytes [2]. In their study, H9c2 cells were treated with adipocytokine‐free medium (the Adipo‐free group), and with adipocytokines from rat epicardial (central fat group) or limb (peripheral fat group) fat tissues.…”
Section: Conflict Of Interestmentioning
confidence: 99%